Jenis-Jenis Ikan Yang Ditemukan Di Sungai Tabir Kecamatan Tabir Kabupaten Merangin Provinsi Jambi - Iistianah, Iistianah; Lusi Z, S.Si, M.Si, Armein; Junaidi, Indra (STKIP PGRI Sumbar, 2014)
ABSTRACT Tabir river is one of the major rivers and a confluence of several tributaries in Rantau Panjang Subdistrict Tabir, Merangin District of Jambi Province. Recently, many human activities pollute the waters of the Tabir River. Theses of pollution derived from mining stone, sand, gold and other human activities. This research aims to identify the species of fish that live in the Tabir river.The study was conducted from October until November 2013 in the Tabir river. Identification of samples was performed at the Museum of Zoology Department of Biology, Faculty of Mathematics and Natural Sciences Andalas University, Padang. This study used a descriptive survey method.There are 16 species, 6 families and 4 of the order were found, namely: Barbichthys leavis, Epalizeorhynchos kalopterus, Hampala macrolepidota, Labeobarbusfestivus, Mystacoleucusmarginatus, Osteochilus chini, Puntius sp. , Osteochilus pleurotaenia, Rasbora argyotaeniaand Tor tambra (family Cyprinidae). Furthermore, Acantopsis octoactinos offamily Cobitidae of ordo Cypriniformes, Leiocassis robustus, Mystus bimaculatus from family Bragidae, Acrochordonichtys chamaelon of family Siluridae of ordo Siluriformes, Osphronemus gouramy offamily Anabantidae from ordo Labyrinthici. The last species was Tetradon sabahensis of familyTetraodontidae from the ordo of Tetraodontiformes. The results of measurements of physico-chemical factors in the Tabir river were temperature of 26 ° C-27 ° C, pH of6-7 and the flow velocity ranged from 0.098 M/det-0, 0316 M /det.